If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-8(3x+2)=2x-3x
We simplify the equation to the form, which is simple to understand
-8(3x+2)=2x-3x
Reorder the terms in parentheses
+(-24x-16)=2x-3x
Remove unnecessary parentheses
-24x-16=+2x-3x
We move all terms containing x to the left and all other terms to the right.
-24x-2x+3x=+16
We simplify left and right side of the equation.
-23x=+16
We divide both sides of the equation by -23 to get x.
x=-0.69565217391304
| 6x+22= | | A(x)=x(14-x) | | -x+sqrt(2)-2=0 | | -14+3a=-8+4a | | 14+4x+2y=142 | | 2(3.5p+7)=7(p+1) | | 6x+5=10x+40 | | 6x+5=10x+20 | | 15/42.625-2=7/22.625+13/4 | | 4.39=-1.6c+7.59 | | 4x+6+2y+8=142 | | -7n-2=16 | | y^2-6y-5x=-14 | | -0.21=log(x) | | 20+130+p=180 | | 4t+17=7+5f | | 25x^3-10x= | | x^4+4x^2+1=0 | | X=y^2-6 | | -8(2-x)=416 | | 3x+2=96 | | (x-2)squared=50 | | (x^3+x^2+x+1)(13x-9)= | | 6k-16=2k+4 | | (x^4-x^2-2x+6)=0 | | (8-6i)-4=x-(1+yi) | | -3(2p+14)-28=2(p+15)+12 | | 6x-3=4(x+22) | | -11+4n=5-(11+17) | | (x^3-x^2-2)=0 | | .7(-3X-2)=3.5+1 | | -11+4n=5-(11+12) |